2016
DOI: 10.1155/2016/3010594
|View full text |Cite
|
Sign up to set email alerts
|

Management of Ankyloglossia and Breastfeeding Difficulties in the Newborn: Breastfeeding Sessions, Myofunctional Therapy, and Frenotomy

Abstract: The problems of suction in newborns give rise to multiple consequences for both the mother and the newborn. The objective of this paper is to present a case of ankyloglossia (“tongue-tie”) and the suction problems that were treated by a multidisciplinary team. The subject is a 17-day-old male patient, with ankyloglossia and suction problems during breastfeeding (pain in the breastfeeding mother, poor weight gain, and long breastfeeds). The patient followed the circuit established in our centre between the serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 23 publications
1
36
0
8
Order By: Relevance
“…These findings corroborate the literature that reports that ankyloglossia may contribute to the early weaning since the difficulty in suckling can cause discomfort, pain and nipple injury in the mothers; and lower intake of milk in ml for 24 hours in the infants, thus being necessary to be breastfed more frequently (16,20,(22)(23)(24)26) . In addition, it is also stated in studies that the mothers of infants with ankyloglossia reported distress and tension caused by the lack of explanation and advice from health professionals about the consequences of this change in breastfeeding (25) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings corroborate the literature that reports that ankyloglossia may contribute to the early weaning since the difficulty in suckling can cause discomfort, pain and nipple injury in the mothers; and lower intake of milk in ml for 24 hours in the infants, thus being necessary to be breastfed more frequently (16,20,(22)(23)(24)26) . In addition, it is also stated in studies that the mothers of infants with ankyloglossia reported distress and tension caused by the lack of explanation and advice from health professionals about the consequences of this change in breastfeeding (25) .…”
Section: Discussionsupporting
confidence: 89%
“…In the period from 1999 to 2008, a study carried out with the objective of checking the current situation of breastfeeding in the Brazilian capitals and the Federal District revealed a prevalence of 41%, with average duration of exclusive breastfeeding of 54.1 days (1.8 months) and average duration of breastfeeding of 341.6 days (11.2 months) (15) . Although many articles have been published in the last 15 years showing the interference of ankyloglossia with breastfeeding (16)(17)(18)(19)(20)(21)(22)(23)(24) , as well as the importance of the anatomophysiology involved in the coordination of suckling, deglutition, and breathing of newborns for breastfeeding, many factors still need to be evaluated since the duration of breastfeeding lies behind that recommended by the WHO. Most studies report an association between ankyloglossia and maternal complaint of nipple pain for breastfeeding, as well as handling difficulty (16,(18)(19)(20)(21)(24)(25)(26) .…”
Section: Introductionmentioning
confidence: 99%
“…As for the country of origin, two were conducted in Brazil 8,10 , one in the United States 9 , and one in Spain 11 . In Brazil, law no.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the methodological heterogeneity of the articles analyzed, the authors report that breastfeeding may be impaired by ankyloglossia-related suction difficulties [8][9][10][11] . Ankyloglossia in newborns is related to breastfeeding difficulties -infants with such a change have signs of suction difficulties 36.07 times greater than those without this change 12 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ankyloglossia is a common condition affecting up to 10% of newborns (Chandrashekar et al 2014; Veyssiere et al 2015; Yoon et al 2017). The condition presents with an inappropriate fusion of the tongue to the alveolar ridge or floor of the mouth and can have several debilitating consequences, including difficulty with breastfeeding and problems with speech, swallowing, and gaining weight (Chandrashekar et al 2014; Ferrés-Amat et al 2016). Although the condition is readily treatable in human patients, the genetic underpinnings of ankyloglossia remain largely uninvestigated.…”
Section: Introductionmentioning
confidence: 99%